2020
DOI: 10.1038/s41438-019-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits ethylene-induced petiole abscission in tomato (Solanum lycopersicum L.)

Abstract: Abscission is a dynamic physiological process that is ubiquitous in plants and can also be an essential agronomic trait in crops, thus attracting attention from plant growers and breeders. In general, the process of plant organ abscission can be divided into four steps, among which the step to obtain the competence to respond to abscission signals (step 2) is the most complex; however, the molecular mechanism underlying this process remains unclear. In this study, we found that hydrogen sulfide (H 2 S) inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…For qRT-PCR analysis, C. reinhardtii samples were collected after different treatments to extract total RNA using the Trizol reagent (Invitrogen, Carlsbad, CA, USA). First-strand cDNA synthesis and qRT-PCR analysis were performed as described previously ( Liu et al., 2020 ). The primers used for qRT-PCR are listed in Supplemental Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…For qRT-PCR analysis, C. reinhardtii samples were collected after different treatments to extract total RNA using the Trizol reagent (Invitrogen, Carlsbad, CA, USA). First-strand cDNA synthesis and qRT-PCR analysis were performed as described previously ( Liu et al., 2020 ). The primers used for qRT-PCR are listed in Supplemental Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, ET is associated with INFLORESCENCE DEFICIENT IN ABSCISSION (IDA)-mediated floral organ abscission through regulation of the transcription of DNA binding with one finger 4.7 (AtDOF4.7), which can directly impair the expression of the abscission-related gene ARABIDOPSIS DEHISCENCE ZONE POLYGALACTURONASE 2 (ADPG2) in Arabidopsis [ 79 ]. Liu et al (2020) demonstrated that H 2 S also participates in ET-induced petiole abscission of tomato [ 18 ]. The research showed that H 2 S treatment could delay abscission of the tomato petiole, but the situation was reversed when the plants were exposed to an H 2 S scavenger.…”
Section: Roles Of H 2 S At Different Stages Of mentioning
confidence: 99%
“…Moreover, H 2 S treatment reduced the enzymatic activities that modify the cell wall. Along with the expression levels of IAA/AUX family genes ( SlIAA3 and SlIAA4 ), the transcription of genes in the IAA-amino acid conjugate hydrolase (ILR) family ( ILR-L3 and ILR-L4 ) were found to be up-regulated and down-regulated, respectively, in the abscission process, suggesting that H 2 S prevented ET-induced petiole abscission by increasing the content of auxin in abscission zone tissues [ 18 ]. Additionally, Hideo et al (2019) reported that D-Cys, as a physiologically relevant substrate, participates in the process of root abscission and that exogenous application of H 2 S chemical donors or polysulfides can positively induce abscission to cope with environmental stimuli in the water fern Azolla [ 80 ].…”
Section: Roles Of H 2 S At Different Stages Of mentioning
confidence: 99%
See 2 more Smart Citations